PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA TOKO ARCHA JAYA GYPSUM - Agusti, Rival; Fadli, Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The purpose of this study is to determine the effect of product quality and price on consumer satisfaction at the Archa Jaya Gypsum Store. This study is a quantitative study with a sample of 98 respondents. The data sources were obtained from secondary data and primary data. This study used a questionnaire as a data collection technique using a purposive sampling method, namely a technique for determining samples with certain considerations or characteristics. The analysis methods used in this study are validity testing, reliability testing, classical heteroscedasticity assumption testing, multiple linear analysis, t-test, F-test and coefficient of determination analysis (R2). The results of this study are Product Quality (X1) has a positive and significant effect on consumer satisfaction (Y), Price (X2) has a positive and significant effect on consumer satisfaction (Y), and Product Quality and Price have a positive and significant effect on consumer satisfaction. Keywords: Product Quality, Price, Consumer Satisfaction Keywords: Product Quality, Pricing, Consumer Satisfaction